African American Religious Life and the Story of Nimrod
XII, 271 p.
Keywords: The biblical text and its key figures have played a prominent role in the development of religious discourse on pressing socio-political issues. Slavery and continued discrimination were given theological sanction through the Old Testament story of Ham, but what of his descendent Nimrod the hunter?